Monthly variance in UK renal transplantation activity: a national retrospective cohort study. Issue 9 (17th September 2019) - Lowe, Marcus; Maidstone, Robert; Poulton, Kay; Worthington, Judith; Durrington, Hannah J; Ray, David W; van Dellen, David; Asderakis, Argiris; Blaikley, John; Augustine, Titus
Abstract : Objective: To identify whether renal transplant activity varies in a reproducible manner across the year. Design: Retrospective cohort study using NHS Blood and Transplant data. Setting: All renal transplant centres in the UK. Participants: A total of 24 270 patients who underwent renal transplantation between 2005 and 2014. Primary outcome: Monthly transplant activity was analysed to see if transplant activity showed variation during the year. Secondary outcome: The number of organs rejected due to healthcare capacity was analysed to see if this affected transplantation rates. Results: Analysis of national transplant data revealed a reproducible yearly variance in transplant activity. This activity increased in late autumn and early winter (p=0.05) and could be attributed to increased rates of living (October and November) and deceased organ donation (November and December). An increase in deceased donation was attributed to a rise in donors following cerebrovascular accidents and hypoxic brain injury. Other causes of death (infections and road traffic accidents) were more seasonal in nature peaking in the winter or summer, respectively. Only 1.4% of transplants to intended recipients were redirected due to a lack of healthcare capacity, suggesting that capacity pressures in the National Health Service did not significantly affect transplant activity. Conclusion: UK renal transplant activity peaks in late autumn/winter in contrast to other countries. Currently, healthcare capacity, though under strain, does not affect transplant activity; however, this may change if transplantation activity increases in line with national strategies as the spike in transplant activity coincides with peak activity in the national healthcare system.